Non-Microbicidal Control of Bacterial Biofilms with Small Molecules - Worthington, Roberta J.; Richards, Justin J.; Melander, Christian (Anti-Infective Agents, 2014)
Bacterial biofilms are defined as a surface attached community of bacteria embedded in a matrix of extracellular polymeric substances that they have produced. When in the biofilm state, bacteria are more resistant to antibiotics and the host immune response than are their planktonic counterparts. Biofilms are increasingly recognized as being significant in human diseases such as; lung infections of cystic fibrosis (CF), colitis, urethritis, conjunctivitis, otitis, endocarditis, and periodontitis. Given the prominence of biofilms in infectious diseases, there has been an increased effort toward the development of small molecules that will modulate bacterial biofilm development and maintenance. In this review, we highlight the development of small molecules that inhibit and/or disperse bacterial biofilms through non-microbicidal mechanisms. The review provides a general overview of how bacteria develop into biofilm communities, why they are important, and the regulation of this process by quorum sensing. This is followed by a discussion of the numerous small molecules that have been identified as possessing the ability to control biofilm development.
Keywords: Biofilm